Mobile phone messaging for illicit drug and alcohol dependence: A systematic review of the literature. (5th May 2017) - Tofighi, Babak; Nicholson, Joseph M.; M Neely, Jennifer; Muench, Frederick; Lee, Joshua D.
Abstract: Issues. Mobile phone use has increased dramatically and concurrent with rapid developments in mobile phone‐based health interventions. The integration of text messaging interventions promises to optimise the delivery of care for persons with substance dependence with minimal disruption to clinical workflows. We conducted a systematic review to assess the acceptability, feasibility and clinical impact of text messaging interventions for persons with illicit drug and alcohol dependence.Approach. Studies were required to evaluate the use of text messaging as an intervention for persons who met Diagnostic and Statistical Manual of Mental Disorders, 4th edition criterion for a diagnosis of illicit drug and/or alcohol dependence. Authors searched for articles published to date in MEDLINE (pubmed.gov ), the Cochrane Library, EMBASE, CINAHL, Google Scholar and PsychINFO.Key Findings. Eleven articles met the search criteria for this review and support the acceptability and feasibility of text messaging interventions for addressing illicit drug and alcohol dependence. Most studies demonstrated improved clinical outcomes, medication adherence and engagement with peer support groups. Text messaging interventions also intervened on multiple therapeutic targets such as appointment attendance, motivation, self‐efficacy, relapse prevention and social support.Implications. Suggestions for future research are described, including intervention design features, clinician contact, privacy measures and integration of behaviour change theories.Conclusion. Text messaging interventions offer a feasible platform to address a range of substances (i.e. alcohol, methamphetamine, heroin and alcohol), and there is increasing evidence supporting further larger‐scale studies. [Tofighi B, Nicholson JM, McNeely J, Muench F, Lee JD. Mobile phone messaging for illicit drug and alcohol dependence: A systematic review of the literature. Drug Alcohol Rev 2017;36:477‐491]